Дослідження Гетьманської столиці у 2009 р. - Коваленко, В.В.; Мезенцев, В.І.; Ситий, Ю.М. (Археологічні дослідження в Україні, 2010)
In 2009, the International Ukrainian-Canadian expedition continued investigation of archaeological monuments on the territory of the Baturyn State Historic and Cultural Preserve «Hetman’s Capital», on the territory of the Fortress and at the out-of-town Hetman Mazepa’s residence in Honcharivka. In particular, excavations of the remains of the foundations of the Church of the Life-giving Trinity have been finished and 65 burials of the 17th and 18th centuries have been investigated along its south wall. Research of the Hetman’s stone palace was ongoing on the territory of the out-of-town residence of Ivan Mazepa in Honcharivka. A foundation ditch from a wooden living (sleeping) construction synchronous with the palace was found nearby and the South-Western bastion of the homestead was also investigated.